Answer:
plug in -3 where any x is in the equation. I reccomend doing it in parenthesis just so things work out nicely
Step-by-step explanation:
![x^2-x^3\\(-3)^2-(-3)^3\\(-3*-3)-(-3*-3*-3)\\(9)-(-27)\\9+27\\36](https://tex.z-dn.net/?f=x%5E2-x%5E3%5C%5C%28-3%29%5E2-%28-3%29%5E3%5C%5C%28-3%2A-3%29-%28-3%2A-3%2A-3%29%5C%5C%289%29-%28-27%29%5C%5C9%2B27%5C%5C36)
638272 is the radius I think
I believe your answer would be B, Bisect AB, but not be perpendicular to it.
Certin, because they can be any two cards.
Answer:
82.8 in²
Step-by-step explanation:
The surface area a triangular based pyramid :
Base area + 1/2(perimeter * slant height)
Base = 8 inches ; Slant height = 4.6 inches ; altitude of base measure = 6.9 inches
Base area of triangle :
1/2 * base * height
1/2 * 8 * 6.9
4 * 6.9
Base area = 27.6 in²
The perimeter, P = sum of sides ; (s1 + s2 + s3
P = 8 + 8 + 8 = 24 in
Hence,
Surface area = 27.6 in² + 1/2(24*4.6)
Surface area = 27.6 in² + (12 * 4.6) in²
Surface area = (27.6 + 55.2)
Surface area = 82.8 in²